The Effect of Online Learning on Intrinsic and Extrinsic Learning Motivation During the Covid-19 Pandemic - Izza, Risma Rosyidatul '; Wahyuni, Sri (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This study aims to test three hypotheses: 1) The influence of online learning on intrinsic learning motivation, 2) The influence of online learning on extrinsic learning motivation, and 3) The influence of online learning on learning motivation during the COVID-19 pandemic. The research design used is quantitative ex post facto. Forty-two (42) seventh-grade students at Mts Miftahul Huda, Kediri, participated in this study. Data were collected through two types of questionnaires: an online learning questionnaire and a learning motivation questionnaire. Data analysis was conducted using simple linear regression analysis and t-tests. The results of the study indicate that: 1) There is a significant influence of online learning on intrinsic learning motivation, with an effect of 22%; 2) There is a significant influence of online learning on extrinsic learning motivation, with an effect of 12.4%; 3) There is a significant influence of online learning on learning motivation during the COVID-19 pandemic, with an effect of 24.3%.